If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4x + -18) + 3x = 6 Reorder the terms: -2(-18 + 4x) + 3x = 6 (-18 * -2 + 4x * -2) + 3x = 6 (36 + -8x) + 3x = 6 Combine like terms: -8x + 3x = -5x 36 + -5x = 6 Solving 36 + -5x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -5x = 6 + -36 Combine like terms: 36 + -36 = 0 0 + -5x = 6 + -36 -5x = 6 + -36 Combine like terms: 6 + -36 = -30 -5x = -30 Divide each side by '-5'. x = 6 Simplifying x = 6
| -3x+18=3x-18 | | 0.12=3h | | 17=x/2+15 | | 5+x/6=-8 | | X+(3/2)=(-3/5) | | [3x-5]+4=14 | | 1/7x-5=7 | | 9+x/3=27 | | y=x^3-3x^2-7x+33 | | 19*.20= | | 4(3+3x)-2=34 | | 4x-13+3x=2+7x-15 | | 10x^2-10x-1=0 | | 2(c-5)-2=8+c | | 9-9x-6-3x=6 | | 10-3(2x-7)=5x-24 | | -8.1-4z-6.6-z=-4z+12.9 | | 7n-21+3n+15=10 | | 39=3 | | -6Y+9(-6Y+6)=7+9(5-Y) | | x+x/2-16=135 | | 9(y-6)=8(8+y) | | -15b+15b=0 | | 20+9(4x-4)=10(2x-1) | | 3(5cx+y)=14cx-6yforx | | x/9+5=-6 | | (7a+3)-(a+5)=-16 | | 3(5cx+y)=14cx-6y | | x+(x+2)+(x+4)+(x+6)+(x+8)=30 | | 25=y-50 | | x/9+5-6 | | 0.30(30)+0.15x=0.20(30+x) |